Strengthening District Health Teams Capacity in Surveillance Systems and Response to Public Health Threats in Western Uganda through Field Epidemiology Training Program (FETP): Recent Advances and Development - Tumwebaze, Mathias; Solomon, Asiimwe; Tukahirwa, Anna; Kamukama, Saul (Current Topics in Medicine and Medical Research Vol. 13, 2021)
Aim: To strengthen the District Capacity in surveillance for effective detection, Reporting and Response to Public Health threats. Background: The overall aim of a good surveillance system is to strengthen the capacity of a Health system through training of health personnel who can conduct effective surveillance activities. A good surveillance system is achieved through improved use of complete and timely health information to detect changes in time to institute a rapid response to the suspected outbreak of Public Health events. This assessment followed a 3-month Field Epidemiology Training program undertaken by the investigator who applied the acquired knowledge and skills in completion of the assessment. Study Design: It was a descriptive cross-sectional, institutional based epidemiological investigation conducted at district level and Health Centre 1V in Kabarole from 15th December 2019-March 2020. eReports were retrieved from DHIS-2 for epidemiological weeks 44 in 2019 to week 3 in 2020. Data Analysis: Micro soft word excel program was used to determine the reporting rates, epidemic disease trends and construction of malaria channel. SWOT analysis was done to identify poor HMIS reporting as the lead surveillance quality challenge and route cause analysis done to determine underlying causes. Results: Weekly reports analyzed were from a total of 53 Health facilities and one Health Centre four for malaria channel construction. Of the 53 functional Health facilities assessed in the district, the average reporting Timeliness was 32% and Completeness at 63% from week 44 in 2019 to week 3 in 2020. This finding shows that the district was not achieving the 80% Timeliness and 80% Completeness national target. The poor reporting situation implies that the district may not detect an emerging Public Health Event and respond in time. Poor reporting rate was linked to knowledge gap among reporting staff in completion of the newly revised HMIS tools and lack of support supervision. The analyzed data revealed that the district had increased dysentery, measles and typhoid fever cases. The dysentery and typhoid fever cases had reached and surpassed the Alert and Action thresh hold levels however there was no reported death from these diseases. Further inquiry revealed that Typhoid fever was being diagnosed using WIDAL test as opposed to WHO recommendation of stool or blood culture. Health facilities diagnose typhoid fever by Widal test instead of doing blood or stool culture and this creates theoretical out breaks. The noted typhoid fever outbreak in the district was therefore being based on wrong laboratory tests hence regarded by the researcher as speculative. Findings on malaria channel revealed a normal and expected trend of malaria in Kabarole district in 2020. Conclusion: Knowledge and skills from FETP-training enabled the investigator to establish the fact that the district’s surveillance system was less sensitive in detecting Public Health events for a quick response. Intensified targeted support supervision and mentorships of all health workers on reporting could help improve the districts surveillance system.